Comparative Analysis of Memristor based Synaptic Circuits for Neuromorphic Architectures - Budhathoki, Ram Kaji (SCITECH Nepal, 2018)
Memristor is one of the fundamental electrical elements, which has recently been successfully built. Memristor is being used extensively as synapses in neuromorphic applications. A common method for developing memristor based synaptic circuits is to store synaptic weight values within memristors as resistance values. It requires use of the continuous resistance (memristance) range available in the memristors to store the weights. In this paper, we study how different compact synaptic circuits implemented using Ti02 memristors to perform zero, negative, and positive synaptic weightings. Results of different memristor based circuits, based on pulsed input signals, are compared, analyzed and presented using Ti02 memristors via simulations.